Convergencias y divergencias entre sistema productivo y sistema educativo - García Ruiz, María Rosa (Revista Complutense de Educación, 2008)
The aim of this study is to find out convergences and divergences between production system and education system in the state of Cantabria (Spain). This article presents the results of a descriptive study and draws a conclusion after interviewing local training specialists. Based on the thesis that both, production system and education system, contribute to economic and social development when there is a balance between the two, data analysis provides us with information on key aspects such as technical training offer, demand for qualified workers, specific characteristics we should take into account when designing and implementing training plans depending on the subsystem and ways to detect workers’ training needs.
Keywords: Permanent training; Demand of qualified professionals; Training opportunities